Tensile and low-cycle fatigue performance of bimetallic steel bars with corrosion. (November 2021) - Hua, Jianmin; Fan, Haifeng; Xue, Xuanyi; Wang, Fei; Chen, Zengshun; Huang, Lepeng; Wang, Neng
Abstract: For reinforced-concrete (RC) structures in a corrosive environment, corrosion tends to occur in the reinforcement, which has a significant adverse effect on the durability. Increasing the corrosion resistance of the reinforcement can substantially enhance the durability of RC structures. Therefore, a bimetallic steel bar (BSB) consisting of stainless steel (cladding layer) and carbon steel (substrate) is proposed. Considering that earthquakes are common natural disasters, load-bearing RC elements with corrosion issues may be subjected to seismic loads. For accurately predicting the seismic resistance of RC structures in service, it is useful to investigate the low-cycle fatigue performance of corroded reinforcements. To address this issue, the tensile and low-cycle fatigue performance of BSBs was investigated experimentally. An electrochemical accelerated corrosion test was conducted to obtain BSB specimens with predetermined corrosion ratios. The corrosion morphologies of the BSB specimens were studied. The mechanical and failure performance was evaluated via the tensile coupon test. The test results indicated that an increase in the corrosion ratio led to a reduction in the tensile performance of the BSB specimens. Predictive equations were proposed for the corroded BSB specimens. After the low-cycle fatigue test, the hysteresis loops of the BSB specimens were obtained, which indicated that corrosion adversely affected the low-cycle fatigue performance. Predictive equations were proposed for determining the number of cycles to failure and the total energy dissipation of the corroded BSB specimens. Increasing the corrosion ratio significantly shortened the steady stages of the maximum tensile and compressive loads. According to the results for the failure performance of BSB specimens with different corrosion ratios under low-cycle fatigue loading, increasing the corrosion ratio reduced the area of the fracture development zone and increased the area of the fracture zone. Highlights: Effects of corrosion on tensile properties of BSBs with different cladding-layer thicknesses and diameters were examined. Low-cycle fatigue properties of BSB specimens with different corrosion ratios were investigated experimentally. Failure performance of BSB specimens under tensile and low-cycle fatigue loading was discussed.